LANJUT USIA: ANTARA TUNTUTAN JAMINAN SOSIAL DAN PENGEMBANGAN PEMBERDAYAAN - Eko Sriyanto (Jurnal Kawistara, 2012)
Social service and social security for elderly in 2010 only covered 143.131 person (Direktorat PSLU,2010) from expectation to serve 2,4 million elderly, whether it is poor and neglected elderly (BPS, 2010).Government capacity to serve social service and social security is limited, so it needs a new strategyto keep the sustainability of elderly’s life. We must have alternative way to assist them to solve theirpsychosocial and physical vulnerability through empowerment scheme. The psychosocial vulnerabilityof elderly is vulnerability that comprise from economic, social and psychological aspects so that it needscomprehensive understanding to make a program for them. Empowering the elderly will create activitythat will be advantageous for them to use the leisure, create social relationship, decrease felt of loneliness,keep reciprocal relationships with their social environment, increase income, and build their capacity inboth health and skills. The development of a sense of empowerment must consider several aspecteds,including environmental characteristics, social-demographic structures, and cross-generational actors.Alternatives for empowerment programs include productive activities (care housing and non-carehousing) and social activities (volunteering).